Understanding Economic Behavior Across Genders: The Role of Financial Literacy and Savings in Retirement Planning - Yastiti, Ni Made Juni; Suci, Ni Made; Telagawathi, Ni Luh Wayan Sayang (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to examine the moderating role of gender on the effect of financial literacy and saving behavior on pension fund planning of non-civil servant government employees (PPNPN) Universitas Pendidikan Ganesha. This research is causal quantitative research (cause and effect) using the survey method in data collection. The instrument used in this study was a questionnaire distributed to 184 samples. The data analysis technique used is descriptive analysis with Partial Least Square (PLS) based on the Structural Equation Model (SEM) analysis method. The results showed a positive and significant effect of financial literacy on retirement planning, saving behavior has a positive and significant effect on retirement planning, gender does not moderate the effect of financial literacy on retirement planning, and gender does not moderate the effect of saving behavior on retirement planning.